PENGGUNAAN TANDA LUAR RUANG DAN FUNGSINYA DI KECAMATAN DENPASAR BARAT - Ida Ayu Pristina Pidada (Widyadari : Jurnal Pendidikan, 2021)
This study aims to reveal the use of outdoor signs and its function in West Denpasar district by using the analysis of Linguistic Landscape by Landry and Bourhis. The data were taken from some holy places in West Denpasar district. The data were classified by variations of writing system and function in landscape linguistics. The data were analyzed by one of concepts from Landry and Bourhis, the language is used as sign in advertisement, billboard, name street which is combined to form linguistic landscape of a given territory and agglomeration. The result of study is showed that most of the variation of writing system use two and three languages. Informational function is showed the information in its sign and symbolize function is showed that culture, political, economic relation.